Anesthesia Technique and Outcomes of Mechanical Thrombectomy in Patients With Acute Ischemic Stroke. Issue 2 (February 2017) - Bekelis, Kimon; Missios, Symeon; MacKenzie, Todd A.; Tjoumakaris, Stavropoula; Jabbour, Pascal
Abstract : Background and Purpose—: The impact of anesthesia technique on the outcomes of mechanical thrombectomy for acute ischemic stroke remains an issue of debate. We investigated the association of general anesthesia with outcomes in patients undergoing mechanical thrombectomy for ischemic stroke. Methods—: We performed a cohort study involving patients undergoing mechanical thrombectomy for ischemic stroke from 2009 to 2013, who were registered in the New York Statewide Planning and Research Cooperative System database. An instrumental variable (hospital rate of general anesthesia) analysis was used to simulate the effects of randomization and investigate the association of anesthesia technique with case-fatality and length of stay. Results—: Among 1174 patients, 441 (37.6%) underwent general anesthesia and 733 (62.4%) underwent conscious sedation. Using an instrumental variable analysis, we identified that general anesthesia was associated with a 6.4% increased case-fatality (95% confidence interval, 1.9%–11.0%) and 8.4 days longer length of stay (95% confidence interval, 2.9–14.0) in comparison to conscious sedation. This corresponded to 15 patients needing to be treated with conscious sedation to prevent 1 death. Our results were robust in sensitivity analysis with mixed effects regression and propensity score–adjusted regression models. Conclusions—: Using a comprehensive all-payer cohort of acute ischemic stroke patients undergoing mechanical thrombectomy in New York State, we identified an association of general anesthesia with increased case-fatality and length of stay. These considerations should be taken into account when standardizing acute stroke care. Abstract : Supplemental Digital Content is available in the text.